Pós-tratamento de efluente de reator anaeróbio por meio de wetlands construídos e filtração lenta - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Concern about water scarcity has led to studies on new technologies used in wastewater treatment, both for environmental preservation and in relation to the possibility of reuse. Thus, this work studied the influence of different hydraulic application rates (HAR) and organic loading rates (OLR) for Vertical Flow Constructed Wetlands (VFCW) associated with slow double filtration (DF) as a technology for the post-treatment of UASB reactor effluent for reuse. A system involving two WCFVs was set up on a pilot scale using sand and pebbles as filter media and reed spp as a plant. This system was associated with a DF which had a first filter made of sand and a second made of activated carbon and zeolite. The rates studied were 200 mm.d-1/ 26,8 g COD/m2; 400 mm.d-1/ 56 g COD/m2 and 600 mm.d-1/ 94,87g COD/m2; with 4 days on and 3 days off. Physico-chemical and microbiological analyses were carried out. The results after going through WCFV showed that for TAH of 200 mm.d-1, the reductions were 93,53% COD 97.2% BOD; 92,24% turbidity; 99,99% true color; 91,07% apparent color; 36,49% NTK; 36.2% N NH3; 66,6% Ph; 14,28% PT; 62,5% E- coli and an increase of more than 100% in NO2 due to nitrification. At 400 mm.d-1, the reductions were 90,56% COD; 96,4% BOD; 60,9% turbidity; 93,75% true color; 34,71% apparent color; 31,4% NTK; 33,38% N NH3; 93,75% E-coli, and an increase in the concentrations of phenols, PT, NO3 and NO2. For the TAH of 600 mm.d-1, there were reductions of 88% COD, 52,4% BOD; 65,93% turbidity; 51,72% true color; 55,65% apparent color; 11,28% NTK; 32,72% N NH3; 17.5% PT; and an increase in the concentration of phenols, NO3, NO2 and E-coli. The higher the TAH, the worse the removal results. After DF with a filtration rate of 13m3.m2.day, regardless of the TAH, there was an increase in the removal of all parameters, with an emphasis on 99.9% in NTK, NO3, NO2, phenols, PT and 10 5 E-coli for the TAH of 200mm.d1. Thus, it can be concluded that the DF made it possible to increase the efficiency of the WCVF and it was also possible to produce effluent for non-potable urban, agricultural, forestry, environmental and industrial reuse according to CERH Resolution No. 122/2023 of the state of Paraná/PR and meets all the reuse possibilities, except potable, in the international legislation EPA/600/R- 12/618.
Keywords: Reuso da água; Wetlands Construídos; Dupla filtração lenta; Química